Theology in the university: ecclesial matter or public matter? - Passos, João Décio (2016)
The article verifies the hypothesis of public Theology from a historical, epistemological and political points of view. The concept refers to legitimation processes of Theology as a “normal science” within the scope of modern institutions, particularly in the university. For its nature, Theology surpasses the ecclesiastic spaces in which it is naturally inserted. In the Brazilian context, it still needs a clear exposition of its epistemological status, so full legitimacy can be acquired beyond the political legitimation already accomplished.